Knowledge and Risk Factors Regarding Type 2 Diabetes among Saudi Population in Jeddah - Shori, Amal Bakr; Alshareef, Hadeel (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: Public awareness of type 2 diabetes is a requirement for individuals and communities to help prevent the disease. Therefore, this study aimed to assess the level of knowledge and awareness of type 2 diabetes among diabetic and non–diabetic persons in Jeddah region, Kingdom of Saudi Arabia (KSA). Materials and Methods: A structured questionnaire was established and a total of 325 respondents (male = 180 and female = 145) have joined this study and descriptive analysis was used to evaluate the knowledge and attitude of the respondents. Results: There was 44.0% of respondents who did not know the difference between diabetes type 1 and 2. The level of awareness about type 2 diabetes in Saudi Arabia ranged between good and very good with 37.8% and 28.9% respectively. More than 50% of respondents did know the important combination of drugs, diet, and physical activity in type 2 diabetes treatment. The respondents have below-average knowledge regarding risk factors, symptoms, and prevention of type 2 diabetes. Furthermore, the respondents (39.4%) have the misconception that diabetes can be cured. However, they were awarded that modification of lifestyles could control type 2 diabetes. Conclusion: Diabetes education should be taken into consideration to increase awareness regarding the risk factors of type 2 diabetes in Saudi Arabia.
Keywords: Type 2 diabetes; Saudi Arabia; Knowledge; Risk factors; Control; Awareness